If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 6 + 6x = -50 Reorder the terms: 6 + X + 6x = -50 Solving 6 + X + 6x = -50 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + X + -6 + 6x = -50 + -6 Reorder the terms: 6 + -6 + X + 6x = -50 + -6 Combine like terms: 6 + -6 = 0 0 + X + 6x = -50 + -6 X + 6x = -50 + -6 Combine like terms: -50 + -6 = -56 X + 6x = -56 Add '-6x' to each side of the equation. X + 6x + -6x = -56 + -6x Combine like terms: 6x + -6x = 0 X + 0 = -56 + -6x X = -56 + -6x Simplifying X = -56 + -6x
| 2-2x=-4(-5x+5) | | -x-29=13+12x | | 24-128-12= | | 4(-7x+3y-2z)= | | (9d+8d)+21=157 | | -4x+6=-22 | | x+30=3x+8 | | x^2-49=49 | | 2(3b+4)-(b-5)= | | x+15=2x | | 5t-4s-3(2t-3s)= | | 36-5x+3= | | (15m-9m)-73=13 | | x+5y=10 | | -(5y+4)-(-4y-7)=-2 | | 146=-7x-5x+2 | | 3(r+1)-(2(3-2r)-3(3-r))=2(r+5)-4 | | 5s+10t=39 | | W^2+9=6w | | 9x-35=2x | | 53=6x-2x+9 | | s=2pirh | | -15=-13+x | | 3x^2+24x+36=0 | | 4z+8=12 | | 2x+2y=9 | | 12x^2-18x=0 | | 12.6=x-7.5 | | 4x^2+16x+12=0 | | -4(2-9n)= | | 7x+8=10x-1 | | 18-2x=5(x-2)-3x |